The Improvement of Flip (2,2) Visual Cryptography Images Using Two Key Images - Dewi, Ratna; Sari, Putri Kartika (ComTech: Computer, Mathematics and Engineering Applications, 2016)
The Flip (2, 2) Visual Cryptography (FVC) is one of the techniques used to encrypt the two secret images into two dual purpose transparencies. The two transparencies can be sent to the objective person. The first secret images can be obtained by stacking the two transparencies and the second secret images can be obtained by stacking the one transparency with the flipping other transparency. Unfortunately, the result decryption processes still have noise and the quality of decrypted secret image is not as same as original secret image. This article proposed the new algorithm to improve the quality of decryption secret image. In this process, the two secret images from decryption process were compared with the two original secret images. The different values of each pixel, which was counted from subtraction of decryption image and original secret images, will be inserted to the two key images. The experimental results of this improvement have a good similarity. The noise in decryption process can be eliminated so the two secret images reconstruction similar to the original secret images.